Self-Silencing and Mental Well-being in Married Individuals - Naeem, Amara; Bashir, Jawaria; Qureshi, Amarah; Saleem, Rabia (Applied Psychology Review, 2024)
The present study investigated the relationship between self-silencing, co-dependency and mental wellbeing in married individuals. The objectives of this study were to explore the relationship between self-silencing, codependency and mental wellbeing in married individuals; and to investigate the mediating role of co-dependency between self-silencing and mental wellbeing in them. The total sample of the study comprised of 154 married individuals, including equal number of men and women, selected through convenient sampling strategy. The survey forms were sent online to the participants via interactive social media networks. Data was collected from the participants using the Mental Health Continuum Short Form, Self-Silencing Scale, and Spann Fischer Co-Dependency Scale. Pearson Product Moment correlation was computed which revealed a positive correlation between self-silencing and codependency, and a negative correlation between self-silencing, codependency and mental wellbeing in married individuals. Co-dependency was found to be the negative predictor of mental wellbeing. Moreover, co-dependency was found to be a significant mediator between self-silencing and mental wellbeing. These findings contribute to the behavioral sciences by providing evidence that the experience of self-silencing and co-dependency can negatively affect mental well-being of married individuals. As a result, it may impact their intimate marital bond.